2000
DOI: 10.1080/10473289.2000.10464239
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ambient Measurements To Identify which Precursor Species Limit Aerosol Nitrate Formation

Abstract: A thermodynamic equilibrium model was used to investigate the response of aerosol NO 3 to changes in concentrations of HNO 3 , NH 3 , and H 2 SO 4 . Over a range of temperatures and relative humidities (RHs), two parameters provided sufficient information for indicating the qualitative response of aerosol NO 3 . The first was the excess of aerosol NH 4 + plus gas-phase NH 3 over the sum of HNO 3 , particulate NO 3 , and particulate SO 4 2-concentrations. The second was the ratio of particulate to total NO 3 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 24 publications
7
57
0
Order By: Relevance
“…The prevalence of ambient NH 3 concentrations in excess of ambient nitric acid concentrations at these three sites is consistent with findings from the IMS95 (where Ͼ90% of samples were NH 3 rich) 6,48 and from regional modeling studies. 49 The CRPAQS data show an eightfold gradient in NH 3 concentration and a twofold gradient in nitric acid concentration between the middle of the SJV, represented by Angiola, and the foothills, represented by Sierra Nevada Foothills.…”
Section: Discussionsupporting
confidence: 76%
“…The prevalence of ambient NH 3 concentrations in excess of ambient nitric acid concentrations at these three sites is consistent with findings from the IMS95 (where Ͼ90% of samples were NH 3 rich) 6,48 and from regional modeling studies. 49 The CRPAQS data show an eightfold gradient in NH 3 concentration and a twofold gradient in nitric acid concentration between the middle of the SJV, represented by Angiola, and the foothills, represented by Sierra Nevada Foothills.…”
Section: Discussionsupporting
confidence: 76%
“…The samples that are thought to be furthest from equilibrium were excluded from the analysis. 39,45 Nearly all samples showed that particulate NO 3 Ϫ concentrations would decrease in response to a 20% reduction of HNO 3 ; in many cases, the predicted decrease was close to 20% ( Figure 8 sites, the mean Sunday NMHC was 3% lower than the mean weekday NMHC at the times of peak O 3 , and 16 -30% lower at other times. Twenty of 28 SoCAB sites (28 of 78 total sites) showed statistically significant (p Ͻ 0.01) higher mean Sunday than weekday O 3 levels; 49 of the remaining 50 sites showed no significant differences between mean weekday and Sunday peak O 3 levels.…”
Section: Weekday and Weekend Differences In Ambient Species Concentramentioning
confidence: 99%
“…40 -44 in conjunction with examination of the ambient measurements. 39 Here, the measurements from the 1-yr PTEP study are analyzed.…”
Section: Weekday and Weekend Differences In Ambient Species Concentramentioning
confidence: 99%
“…The slope of this regression line was 1.65, indicating an excellent ion balance and the presence on Nylon filters of NH 4 NO 3 and NH 4 Cl as constituent of the total fine particles. In addition, using the approach of Ansari and Pandis (1998) and of Blanchard et al (2000) it is possible to calculate the excess NH 3 , which represents the quantity of NH 3 that would remain after complete neutralization of available aerosol and acid gases, is defined as:…”
Section: Temporal Variationmentioning
confidence: 99%